Halal assurance climate creation in processing products for micro waqf bank customers - Muhamad Fauzi; Mahmudin Mahmudin; Fadhli Fathul Haq (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — Halal assurance guides Muslims in production and consumption to create a strong belief in utilizing it. This study analyzes the halal assurance climate creation and sharia social financing from micro waqf banks.Method — The research used a qualitative method with a case study approach at the Lan Taburo micro waqf bank, Lebak regency, Banten province, Indonesia. Data sources from managers and customers of food processing businesses using interview techniques and data analysis using triangulation.Result — The research shows that micro waqf banks need instruments like desire to engage in the halal assurance process, becoming the key requirement for customers, incentives for registration, education, and training, direction and monitoring, and evaluation of halal assurance evaluations.Micro waqf banks are sharia social and financial institutions providing financing and micro-small entrepreneurs assistance for productive communities. It is necessary to increase the awareness of managers and customers regarding the importance of halal assurance as an integration of sharia social financing.Contribution — This study recommends the government or financial services authority to implement halal assurance as a requirement for micro waqf bank customers to encourage small micro-entrepreneurs by creating a climate of halal assurance for the processing products.